Strengthening Public Financial Management Reform in Pacific Island Countries - World Bank Group; New Zealand Ministry of Foreign Affairs and Trade; Australian Department of Foreign Affairs and Trade; Overseas Development Institute (World Bank, Washington, DC, 2016)
The Pacific Financial Technical Assistance Center (PFTAC) produced ‘A Public Financial Management Roadmap for Forum Island Countries’ (“The Roadmap”) in 2009 (PFTAC 2010). This document was adopted at the Forum Economic Ministers’ Meeting (FEMM) of the Pacific Island Forum as an agreed approach to Public Financial Management (PFM) reform in Forum Island Countries. The document established the need for regular Public Expenditure and Financial Accountability (PEFA) assessments and the development of PFM reform plans for Pacific countries based on PEFA assessments and other inputs. Based on international experience, the document concluded that PFM reforms in Pacific countries should, among other things: i) reflect country priorities; ii) take account of country constraints, including capacity constraints; and iii) have strong country ownership and take political dimensions into account.Five years on from the adoption of the Roadmap, this report examines experiences of PFM reform in two Pacific island countries in order to inform future improvements.This report does not assess current PFM systems in case study countries. Rather, it provides an analysis of previous experiences with PFM reforms, focusing on the research period 2010-2014. PFM problems identified in this report may have since been resolved. The recommendations of the Roadmap reflect that capacity constraints are a defining feature of government in Pacific island countries.There is a growing consensus regarding the importance of prioritization in Pacific PFM reform.Building on the recommendations of the Roadmap, this report draws on recent literature regarding ‘problem-driven approaches’ to further inform analysis of and recommendations for prioritization of PFM reforms. This report represents the conclusions of joint work between the World Bank, the New Zealand Ministry of Foreign Affairs and Trade, and the Australian Department of Foreign Affairs and Trade, and the Overseas Development Institute.